Development of an Automatic Braking Mechanism Using Arduino, LiDAR, and Infrared Sensors to Improve Motorcycle Safety - Ninuk Jonoadji; Ian Hardianto Siahaan; Michael Felix Wong (Universitas Islam Raden Rahmat, Malang, 2026)
The high number of motorcycle accidents due to rider negligence confirms the need for an active safety system that is able to respond to emergency conditions, while research on auto-brakes is still limited, especially in terms of the detection distance of objects which are generally only active when there are objects within 9 meters according to sensor calibration and control logic as well as the application in low-speed vehicles at least 5 km/h. This research designed an Arduino Uno-based auto-brake system with LiDAR and infrared sensors to detect objects in front of the vehicle, with a braking mechanism running a servo motor that presses the main brake. The research methods include hardware design, sensor–actuator integration, fuzzy logic programming, and stationary testing using bike-based prototypes with variations in distance and speed. The results showed that the system was able to respond effectively at a distance of 700 cm with a maximum braking angle of 40°, maintaining stability in sudden conditions, thus confirming the effectiveness of fuzzy logic-based auto-brakes in improving rider safety while opening up the direction of further research for two-wheeled adaptive safety systems.